Death do us part - Wong, Caleb Jing Yi (Nanyang Technological University, 2021)
Death Do Us Part is a 18 min 26 sec short film Final Year Project (FYP) produced by JUICY Films. The short film was produced by Caleb Wong, Jena Ong, Ng Yi Yang, Yeo Yong Lun, undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication and Information (WKWSCI), under the supervision of Dr Kym Campbell. This report details the process that the documentary embarked on and highlights the approach, challenges and the individual reflections of the filmmakers.